Determinants of obesity among adolescents in Terengganu : a population study - Nurzaime Zulaily
Obesity among children and adolescents has become epidemic worldwide and more evident in developing countries including in Malaysia. The prevalence has increased substantially every year and has led to adult obesity and other comorbidities. Nonetheless, the actual associated determinants and risk factors among this population, especially in a sub-urban state like Terengganu, remain uncertain. Therefore, the objective of this study was to determine the prevalence of obesity and to explore the relationship between socio-demographic determinants, dietary intake, physical activity (PA) level and physical fitness (PF) level with Body Mass Index (BMI) among school adolescents in Kuala Terengganu and Besut districts. A cross¬sectional study involving 9,624 school adolescents aged 12 years old from 135 govemment primary schools in Kuala Terengganu and Besut districts was carried out from November 2014 to June 2015. Socio-demographics data was collected using self-reported questionnaire whilst data on dietary intake and PA were collected using Food Frequency Questionnaire (FFQ) and children Physical Activity Questionnaire (cPAQ), respectively. Out of 3,798 subjects who retumed the questionnaire, 1,404 subjects with valid data were included in the study. Using a standardised protocol, physical education teachers in each school conducted physical fitness assessment (SEGAK) that includes weight and height measurements, step-up, push-up, sit and reach and partial curl-up tests. Reliability analysis using Intraclass Correlation Coefficient (ICC), Bland-Altman plot and Cohen's Kappa statistics proved that anthropometric data obtained from SEGAK assessments is a reliable source for identification of body weight status among school children and adolescents (Chapter 3).The data were uploaded into a specific Health Monitoring System (HEMS) for data collection and processing. BMI was classified based on WHO BMI-for-age z-scores cut-off. MUltiple linear regression analysis was conducted to determine the associated factors of BMI z-scores. Overall, the prevalence of overweight and obesity were 17.4% and 15.2%, respectively. Parents' weight status, household income level, household size, mother's working status and mother's education level showed significant association with weight status in adolescents (p<0.05). This study found no difference between BMI groups in total energy intake (p=0.837) and PA level i.e. cPAQ score (p=0.09) but found significantly lower PF level i.e. SEGAK score (p<0.001) among obese adolescents as compared to normal-weight adolescents. In addition, multiple linear regression analyses showed that BMI z-score was positively associated with parent's BMI (p<0.001), birth weight (p=0.003), and serving size of milk and dairy products (p=0.036), whilst inversely associated with household size (p=0.022). The R2 of 0.131 indicates that about 13.1% of the variances in BMI z¬scores were explained by parent's BMI, birth weight, serving of milk and dairy products; and household size. In conclusion, the prevalence of overweight and obesity among adolescents in Terengganu were considerably high compared to the national prevalence. The present study had found important relationships between dietary intake and familylhome environment factors among adolescents which could serves as a basis in developing specific preventive strategies that tailored to this population.